Epigenetics of early-life lead exposure and effects on brain development. (December 2012) - Senut, Marie-Claude; Cingolani, Pablo; Sen, Arko; Kruger, Adele; Shaik, Asra; Hirsch, Helmut; Suhr, Steven T; Ruden, Douglas
The epigenetic machinery plays a pivotal role in the control of many of the body's key cellular functions. It modulates an array of pliable mechanisms that are readily and durably modified by intracellular or extracellular factors. In the fast-moving field of neuroepigenetics, it is emerging that faulty epigenetic gene regulation can have dramatic consequences on the developing CNS that can last a lifetime and perhaps even affect future generations. Mounting evidence suggests that environmental factors can impact the developing brain through these epigenetic mechanisms and this report reviews and examines the epigenetic effects of one of the most common neurotoxic pollutants of our environment, which is believed to have no safe level of exposure during human development: lead.